Effectiveness of PjBL Assisted by e-LKPD DTRE on Critical Thinking and Learning Motivation - Khairunnisah Khairunnisah; Lina Aviyanti; Iin Suminar (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study examines the effectiveness of Project-Based Learning (PjBL) assisted by e-LKPD Design Thinking on Renewable Energy (DTRE) in improving students’ critical thinking skills and learning motivation. A quasi-experimental design with a non-equivalent control group was employed. The sample consisted of 35 students in the experimental class (PjBL assisted by e-LKPD DTRE) and 34 students in the control class (PjBL with conventional worksheets) at a senior high school in Bandung. Data were collected using a validated critical thinking test and a learning motivation questionnaire and analyzed using normalized gain (N-gain) and non-parametric statistical tests. The results showed that both groups improved; however, the experimental class achieved a higher N-gain (0.42, moderate) than the control class (0.28, low). A significant difference was found between groups (p < .001) with a moderate effect size (r = 0.443). The highest improvement occurred in the elementary clarification indicator (N-gain = 0.54), indicating that structured project activities supported students in identifying and explaining problems more systematically. Learning motivation was categorized as moderate (66.09%), with the highest score in the relevance dimension (72.22%), suggesting that the learning approach helped connect concepts with real-life contexts. In conclusion, integrating e-LKPD DTRE within PjBL effectively enhances students’ critical thinking skills and supports meaningful and contextual learning, with potential for further refinement to strengthen students’ motivation.